Content validity testing of the INTERMED Self‐Assessment in a sample of adults with rheumatoid arthritis and rheumatology healthcare providers - Kiran Dhiman; Marc Hall; Trafford Crump; Alison M. Hoens; Diane Lacaille; James A. Rankin; Karen L. Then; Glen Hazlewood; Cheryl Barnabe; Steven Katz; Jason Sutherland; Erika Dempsey; et al. (Health Expectations)
Abstract Background Care complexity can occur when patients experience health challenges simultaneously with social barriers including food and/or housing insecurity, lack of transportation or other factors that impact care and patient outcomes. People with rheumatoid arthritis (RA) may experience care complexity due to the chronicity of their condition and other biopsychosocial factors. There are few standardised instruments that measure care complexity and none that measure care complexity specifically in people with RA. Objectives We assessed the content validity of the INTERMEDS Self‐Assessment (IMSA) instrument that measures care complexity with a sample of adults with RA and rheumatology healthcare providers (HCPs). Cognitive debriefing interviews utilising a reparative framework were conducted. Methods Patient participants were recruited through two existing studies where participants agreed to be contacted about future studies. Study information was also shared through email blasts, posters and brochures at rheumatology clinic sites and trusted arthritis websites. Various rheumatology HCPs were recruited through email blasts, and divisional emails and announcements. Interviews were conducted with nine patients living with RA and five rheumatology HCPs. Results Three main reparative themes were identified: (1) Lack of item clarity and standardisation including problems with item phrasing, inconsistency of the items and/or answer sets and noninclusive language; (2) item barrelling, where items asked about more than one issue, but only allowed a single answer choice; and (3) timeframes presented in the item or answer choices were either too long or too short, and did not fit the lived experiences of patients. Items predicting future healthcare needs were difficult to answer due to the episodic and fluctuating nature of RA. Conclusions Despite international use of the IMSA to measure care complexity, patients with RA and rheumatology HCPs in our setting perceived that it did not have content validity for use in RA and that revision for use in this population under a reparative framework was unfeasible. Future instrument development requires an iterative cognitive debriefing and repair process with the population of interest in the early stages to ensure content validity and comprehension. Patient or Public Contribution Patient and public contributions included both patient partners on the study team and people with RA who participated in the study. Patient partners were involved in study design, analysis and interpretation of the findings and manuscript preparation. Data analysis was structured according to emergent themes of the data that were grounded in patient perspectives and experiences.